LOCAL COMMUNITY PARTICIPATION AND ECONOMIC IMPACT OF PENTINGSARI VILLAGE TOURISM YOGYAKARTA - Rani Kusumo Wardani; Jimmy Harry Putu Suarthana (Journal of Applied Management Studies, 2021)
The purpose of this study was to determine and analyze the level of community participation in Pentingsari Village Tourism management Yogyakarta. There aremany activities involve the local communities, such as cooking class, traditional dancing, painting, out bond and local activities likes planting rice and fishing. The level of local people participation is based on the theory of public participation Level (Tosun, 1999), that is categorized into spontaneous, induced and coercive.This study measured the level of participation by Tosun Theory (1999), the same as previous research of Agustini and Suarthana (2016), then analyzed its impact on the economy to local communities. Methodology used in this research are qualitative and qualitative analysis using Partial Least Square (PLS). In depth interview conducted to 8 key informants in managing Pentingsari Village Tourism and 40 respondens whom involved in tourism village activities. The finding of this research is that community participation in tourism activities impact 29,2% to economy. It was generate income, providing employment, increase the amount of production, marketing network and promote the Pentingsari Village Tourism to the world. The implications of this study are to raise the level of community participation in various tourism activities. Thus the local community's economy will improve, the standard of living and welfare of the people is also increasing. Limitations of this study only focus on the economic, social and environment aspects; in fact, many other aspects that rose up as the impact of community participation in tourism activities need to be further analyzed.